Switching to riociguat: a potential treatment strategy for the management of CTEPH and PAH - Raymond L. Benza; Paul A. Corris; Hossein-Ardeschir Ghofrani; Manreet Kanwar; Vallerie V. McLaughlin; Amresh Raina; Gérald Simonneau (Pulmonary Circulation, 2020)
Currently, five classes of drug are approved for the treatment of pulmonary arterial hypertension (PAH): phosphodiesterase 5 inhibitors (PDE5i); endothelin receptor antagonists; prostacyclin analogs; the IP receptor agonist selexipag; and the soluble guanylate cyclase (sGC) stimulator riociguat. For patients with inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH), riociguat is currently the only approved pharmacotherapy. Despite the development of evidence-based guidelines on appropriate use of specific drugs, in clinical practice patients are often prescribed PAH-targeted therapies off label or at inadequate doses. PDE5i are the most often prescribed class of drugs as initial therapy, either alone or in combination with other drug classes. However, a proportion of patients receiving PAH therapies do not reach or maintain treatment goals. As PDE5i and riociguat target different molecules in the nitric oxide-sGC-cyclic guanosine monophosphate (NO-sGC-cGMP) signaling pathway, for patients with PAH without an initial or sustained response to PDE5i, there is a biological rationale for switching to riociguat. However, robust data from randomized controlled trials on the safety and efficacy of switching are lacking, as is formal guidance for clinicians. Here we review studies of sequential combination therapy, and trial data and case studies that have investigated switching between PAH-approved therapies, particularly from PDE5i to riociguat in patients with PAH with an insufficient response to PDE5i, and in patients with CTEPH who were receiving off-label treatment. These studies summarize the current evidence and practical real-life experience on the concept of switching treatments.